Molecular and Biochemical Insights Into Early Responses of Hemp to Cd and Zn Exposure and the Potential Effect of Si on Stress Response - Luyckx, Marie; Hausman, Jean-François; Sergeant, Kjell; Guerriero, Gea; Lutts, Stanley (Frontiers in Plant Science, 2021)
With the intensification of human activities, plants are more frequently exposed to heavy metals (HM). Zinc (Zn) and cadmium (Cd) are frequently and simultaneously found in contaminated soils, including agronomic soils contaminated by the atmospheric fallout near smelters. The fiber crop Cannabis sativa L. is a suitable alternative to food crops for crop cultivation on these soils. In this study, Cd (20 μM) and Zn (100 μM) were shown to induce comparable growth inhibition in C. sativa. To devise agricultural strategies aimed at improving crop yield, the effect of silicon (Si; 2 mM) on the stress tolerance of plants was considered. Targeted gene expression and proteomic analysis were performed on leaves and roots after 1 week of treatment. Both Cd- and Zn-stimulated genes involved in proline biosynthesis [pyrroline-5-carboxylate reductase (P5CR)] and phenylpropanoid pathway [phenylalanine ammonia-lyase (PAL)] but Cd also specifically increased the expression of PCS1-1 involved in phytochelatin (PC) synthesis. Si exposure influences the expression of numerous genes in a contrasting way in Cd- and Zn-exposed plants. At the leaf level, the accumulation of 122 proteins was affected by Cd, whereas 47 proteins were affected by Zn: only 16 proteins were affected by both Cd and Zn. The number of proteins affected due to Si exposure (27) alone was by far lower, and 12 were not modified by heavy metal treatment while no common protein seemed to be modified by both CdSi and ZnSi treatment. It is concluded that Cd and Zn had a clear different impact on plant metabolism and that Si confers a specific physiological status to stressed plants, with quite distinct impacts on hemp proteome depending on the considered heavy metal.